2003
DOI: 10.1063/1.1566931
|View full text |Cite
|
Sign up to set email alerts
|

Electron-stimulated desorption of D2O coadsorbed with CO2 ice at VUV and EUV energies

Abstract: Electron-induced processes in water ice and CO2 ice are important in planetary science. We have measured desorption yields of positive ion products (C+, O+, D+, D3O+, CO+, O2+) produced as a result of exposing pure CO2 and D2O adsorbed on CO2 ices to 10–100 eV (i.e., the vacuum-ultraviolet–extreme-ultraviolet energy region) electron beams. Measurements on pure CO2 ice irradiated with 40-eV electrons suggest that pores in the CO2 ice are responsible for trapping molecular precursors for bimolecular reactions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…33 Our attribution of the higher binding-energy peak in spectra from the slow samples to photoinduced oxidation is supported by results of recent VUV surface photochemical studies of water adsorbed on graphite 35 and CO 2 ice. 36 It was shown that H + ͑D + ͒ and H 3 O + ͑D 3 O + ͒ ion fragments can readily desorb into vacuum, leaving OH species ͑possibly in an excited state͒ trapped at the surface and thus available for silicon oxidation. Desorption of hydrogen from Si surfaces can also be induced under VUV photoirradiation 37,38 and the resultant dangling bonds would be able to act as reaction sites.…”
Section: Fig 5 ͑A͒mentioning
confidence: 99%
“…33 Our attribution of the higher binding-energy peak in spectra from the slow samples to photoinduced oxidation is supported by results of recent VUV surface photochemical studies of water adsorbed on graphite 35 and CO 2 ice. 36 It was shown that H + ͑D + ͒ and H 3 O + ͑D 3 O + ͒ ion fragments can readily desorb into vacuum, leaving OH species ͑possibly in an excited state͒ trapped at the surface and thus available for silicon oxidation. Desorption of hydrogen from Si surfaces can also be induced under VUV photoirradiation 37,38 and the resultant dangling bonds would be able to act as reaction sites.…”
Section: Fig 5 ͑A͒mentioning
confidence: 99%
“…The total desorption yield (molecules/photon) was assessed to be 1.4% at 6 K and 20% at 50–60 K. Direct CO 2 emission from this PSD process was found to be significantly lower than that from Öberg et al, but the studies determined that the CO 2 desorption yield was temperature-, fluence-, and thickness-dependent. Electron irradiation studies of CO 2 ice measured desorption yields of a variety of positive ion products such as C + , O + , D + , D 3 O + , CO + , O 2 + . The authors showed that the production channel of O 2 + was energy-dependent.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In model laboratory studies electrons may originate indirectly from photo-induced processes 8 or from a well defined electron gun source. [9][10][11][12] The motivation for such studies arises from the need to better understand the physics and chemistry at the outer space 13 as well as phenomena occurring at the stratosphere, 14 where solid particles are covered by layers of ice. 15 The interaction of electrons with molecules adsorbed on metal or oxide substrates is often described by the Menzel-Gomer-Redhead (MGR) 16,17 model.…”
Section: Introductionmentioning
confidence: 99%